Recommandations de l’étude de besoins sur les foyers de soins de longue durée du Nord de l’Ontario - Réseau du mieux-être francophone du Nord de l’Ontario (Réseau du mieux-être francophone du Nord de l’Ontario, 2022)

Recommendations from the Northern Ontario Long-Term Care Homes Needs Study - Réseau du mieux-être francophone du Nord de l’Ontario (Réseau du mieux-être francophone du Nord de l’Ontario, 2022)

Pratique # 10 : Les points de service satellites (Ontario) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (2021)

Pratique # 12 : Les Lunchs-causeries au Centre de services communautaires Vanier (Ontario) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (2021)

Pratique # 13 : Une infirmière de Santé publique dans un centre de services communautaires qui assure l’aiguillage des aînés (Ontario) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (2021)

The pharmacist is in: The availability and distribution of French-speaking pharmacists in Ontario - Timony, Patrick E.; Waite, Nancy; Houle, Sherilyn; Violette, Richard; Gauthier, Alain P. (Linguistic Minorities and Society, 2022)
Francophones are an official language minority in Ontario with limited access to linguistically concordant healthcare services. Although communication is an important skill in the field of pharmacy, little is known about the availability of French-speaking pharmacists. This secondary data analysis of the Ontario College of Pharmacists registry converted weekly hours worked into full-time equivalents (FTEs) and calculated ratios of pharmacist FTEs per 1,000 population. French-speaking pharmacists tended to offer fewer FTEs in communities with a larger concentration of Francophones, particularly in northern and rural areas, a trend that was not observed among English-speaking pharmacists. This maldistribution of French-speaking pharmacists may limit the ability of official language minority patients to receive pharmacy services in their language of choice. Keywords: English, pharmacists, Francophones, linguistic concordance, geographic distribution, French-language health services

Pratique # 27 : Accueil centralisé (Centre francophone du Grand Toronto, Ontario) - van Kemenade, Solange; Benoît, Josée; Savard, Sébastien; Savard, Jacinthe (2025)

Pratique # 23 : Navigateur francophone du système de santé (Terre-Neuve-et-Labrador) - van Kemenade, Solange; Michel, Jean Nephetaly; Savard, Jacinthe; Benoît, Josée (2021)